Exploration des activités biologiques des principes actifs de Portulaca oleracea L. extraits par des solvants thérapeutiques eutectiques profonds (STEP) - SEBBAH Tarik (Université de Mostaganem, 2025)
This study explores the design, characterization, and biological evaluation of NADESs for the extraction of active pharmaceutical ingredients (APIs) from Portulaca oleracea leaves (POL), The molecular interactions within NADESs were explored using computational approaches such as density functional theory (DFT) calculations and molecular dynamics (MD) simulations to assess hydrogen bond strength and structural stability. Extraction efficiency of TPC, TFC and CT was significantly higher in all NADESs-POL extracts, comparing them to conventional EtOH-POL extract. HPLC-DAD was employed to isolate major antioxidant compounds, confirming enhanced extraction yields in NADESs compared to EtOH. Antioxidant activity was assessed using anti-radical scavenging assays, revealing significantly lower EC50 values in NADESs-POL compared to EtOH-POL extracts, these findings were further confirmed by Trolox equivalent antioxidant capacity (TEAC). The antimicrobial activity of NADESs-POL was evaluated against Gram-positive and Gram-negative bacterial strains, demonstrating potent bacteriostatic effects, particularly against Staphylococcus aureus and Escherichia coli. Furthermore, the cytotoxic effects of NADESs-POL were investigated in AGS gastric adenocarcinoma cells, indicating a dose-dependent reduction in cell viability. In vivo acute toxicity studies were conducted in Wistar rats to determine the safety profile of selected NADESs, through which 200 μL was determined a safe dose for daily administration. To evaluate the hepatoprotective potential of THEDESs, Wistar rats received 200 μL of NADESs-POL daily for five days, followed by MTX administration (20 mg/kg) to induce hepatotoxicity. Liver function markers and histopathological examinations were performed to assess THEDES efficacy. Among the tested formulations, THEDESs G1 and G7 exhibited the most potent hepatoprotective effects, significantly reducing oxidative stress, inflammatory markers, and endothelial damage while preventing hepatic fibrosis. Histopathological analysis confirmed that THEDESs 1, 3, 4, and 7 effectively prevented hepatic steatosis, whereas THEDESs 5 and 6 were less effective in mitigating sinusoidal congestion. These findings underscore the potential of NADESs as sustainable solvents for extracting and stabilizing bioactive compounds, with THEDESs offering a novel hepatoprotective strategy against MTX-induced liver injury. The integration of computational and experimental approaches highlights the structural and functional advantages of NADESs, paving the way for their application in pharmaceutical formulations and therapeutic interventions.
Keywords: Portulaca oleracea; HPLC-DAD; NADES; THEDES; Hepatoprotection; AGS